2019
DOI: 10.1002/adfm.201906551
|View full text |Cite
|
Sign up to set email alerts
|

Soft Electronics Manufacturing Using Microcontact Printing

Abstract: This work describes a microcontact printing (µCP) process for reproducible manufacturing of liquid gallium alloy-based soft and stretchable electronics. One of the leading approaches to create soft and stretchable electronics involves embedding liquid metals (LM) into an elastomer matrix. Although the advantages of liquid metal-based electronics have been well established, their mainstream adoption and commercialization necessitates development of precise and scalable manufacturing methods. To address this nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 81 publications
(236 reference statements)
0
46
0
Order By: Relevance
“…[13] A few works have presented EGaIn or biphasic EGaIn electrodes directly printed onto carefully designed surfaces, but the resulting electrodes were not deformable. [14][15][16][17][18][19][20][21][22] Herein, we present a highly deformable and self-healable EGaIn electrode that is directly micropatterned onto a hydrogel. Facile spreading of an EGaIn droplet was observed on the surface of a chemically cross-linked hydrogel, allowing for direct pattern-transfer printing of EGaIn and facilitating patterning of a variety of EGaIn electrodes on hydrogels.…”
Section: Doi: 101002/adma202002178mentioning
confidence: 99%
“…[13] A few works have presented EGaIn or biphasic EGaIn electrodes directly printed onto carefully designed surfaces, but the resulting electrodes were not deformable. [14][15][16][17][18][19][20][21][22] Herein, we present a highly deformable and self-healable EGaIn electrode that is directly micropatterned onto a hydrogel. Facile spreading of an EGaIn droplet was observed on the surface of a chemically cross-linked hydrogel, allowing for direct pattern-transfer printing of EGaIn and facilitating patterning of a variety of EGaIn electrodes on hydrogels.…”
Section: Doi: 101002/adma202002178mentioning
confidence: 99%
“…So far, a series of intense investigations have been succeeded. With the time going on, more and more international labs are joining with many outstanding works reported in the area ( Boley et al., 2014 ; Cao et al., 2020 ; Khondoker and Sameoto, 2016 ; Parekh et al., 2016 ; Ma et al., 2019 ; Markvicka et al., 2018 ; Silva et al., 2020 ; Teng et al., 2019 ; Yalcintas et al., 2019 ) which further significantly strengthened the research endeavor.…”
Section: Basic Principles and Key Technologiesmentioning
confidence: 99%
“…Yalcintas et al. [ 45 ] showed that with a precise and accurate printing method, liquid metal capacitors can be made from wires only 15 µm in width. These wires were able to deform and retain their electrical capabilities, with capacitance change being measured against lateral and longitudinal strain.…”
Section: Capacitorsmentioning
confidence: 99%